General Practitioners' and patients' perceptions towards stratified care: a theory informed investigation. Issue 1 (December 2016) - Saunders, Benjamin; Bartlam, Bernadette; Foster, Nadine; Hill, Jonathan; Cooper, Vince; Protheroe, Joanne
Abstract Background Stratified primary care involves changing General Practitioners' (GPs) clinical behaviour in treating patients, away from the current stepped care approach to instead identifying early treatment options that are matched to patients' risk of persistent disabling pain. This article explores the perspectives of UK-based GPs and patients about a prognostic stratified care model being developed for patients with the five most common primary care musculoskeletal pain presentations. The focus was on views about acceptability, and anticipated barriers and facilitators to the use of stratified care in routine practice. Methods Four focus groups and six semi-structured telephone interviews were conducted with GPs (n = 23), and three focus groups with patients (n = 20). Data were analysed thematically; and identified themes examined in relation to the Theoretical Domains Framework (TDF), which facilitates comprehensive identification of behaviour change determinants. A critical approach was taken in using the TDF, examining the nuanced interrelationships between theoretical domains. Results Four key themes were identified: Acceptability of clinical decision-making guided by stratified care; impact on the therapeutic relationship; embedding a prognostic approach within a biomedical model; and practical issues in using stratified care. Whilst within each theme specific findings are reported, common across themes was the identified relationships between the theoretical domains ofknowledge, skills, professional role and identity, environmental context and resources, andgoals . Through analysis of these identified relationships it was found that, for GPs and patients to perceive stratified care as being acceptable, it must be seen to enhance GPs'knowledge andskills, not undermine GPs' and patients' respectiveidentities and be integrated within theenvironmental context of the consultation with minimal disruption. Conclusions Findings highlight the importance of taking into account the context of general practice when intervening to support GPs to make changes to their clinical behaviour. Findings will inform further stages of the research programme; specifically, the intervention format and content of support packages for GPs participating in a future randomised controlled trial (RCT). This study also contributes to the theoretical debate on how best to encourage clinical behaviour change in general practice, and the possible role of the TDF in that process.